Relationship between sleep quality and dietary nutrients in rural elderly individuals: a latent class analysis - Zhao, Xinlei; Xie, Xinyan; Zhou, Han; Zhong, Feng; Liu, Cuiping (Frontiers in Nutrition, 2025)
BackgroundThis study sought to identify sleep patterns in older adults residing in rural regions, as well as investigate the potential influence of dietary nutrient intake on these patterns.MethodsData were collected from a cross-sectional sample of Qingdao Town, Shandong Province, China. The study investigated 1,167 elderly participants using a general questionnaire, the Pittsburgh Sleep Quality Index, the simplified Food Frequency Questionnaire, and 24-h dietary recall methods. Latent profile analysis and binary logistic regression were applied for data analysis.ResultsTwo sleep categories were identified as “Quick falling asleep, long time, high efficiency group,” Class 1(89.1%) and “Difficult falling asleep, short time, low efficiency group,” Class 2(10.9%). In comparison to Class 1, individuals in Class 2 exhibited a higher likelihood of experiencing difficulties in falling asleep quickly and having poor sleep efficiency when consuming less than 50 g/d of potatoes (OR = 1.863, p = 0.034). Conversely, a daily protein intake of 60 g or more (OR = 0.367, p = 0.007), a daily intake of retinol of 700 equivalents or more (OR = 0.212, p = 0.002), and a daily milk intake of 300 g or more (OR = 0.295, p = 0.035) were associated with a greater probability of falling asleep quickly, having longer sleep duration, and experiencing higher sleep efficiency.ConclusionOur analysis identified two distinct sleep quality patterns among elderly individuals in rural areas. The sleep quality of rural elderly individuals is influenced by their dietary habits. The findings demonstrated a positive association between enhanced sleep quality and higher intake of dairy products, potatoes, and foods containing retinol and protein. Therefore, we propose increased consumption of these nutritional sources for the elderly population.